Pola Pendampingan dan Pembelajaran Anak Berkebutuhan Khusus (ABK) di Sekolah Inklusi: POLA PENDAMPINGAN DAN PEMBELAJARAN ANAK BERKEBUTUHAN KHUSUS (ABK) DI SEKOLAH INKLUSI - RADIANI, WIDIYA ARIS (EBTIDA': Jurnal Pendidikan Dasar Islam, 2025)
Inclusive education is very important in providing equal learning opportunities for children with special needs. This study aims to describe the patterns of assistance and learning for children with special needs in inclusive schools. Data were collected using qualitative descriptive methods through observation and interviews involving subject teachers, guidance counselors, and special needs teachers. The results show that the patterns of assistance for children with special needs are based on the principles of love, patience, and repetition to create a comfortable and inclusive learning environment, help children manage their emotions, and understand the consequences of their behavior. Special learning management is tailored through Individual Learning Plans and Programs. Parents play a role by synchronizing home and school rules, monitoring learning, and communicating regularly with teachers. Support is provided through face-to-face interaction and the use of technology. The learning pattern shows that learning evaluations are conducted to assess academic progress and performance. Learning media utilize technology and interactive tools. Individual learning programs are specifically designed according to student needs based on psychological assessments and collaboration. Teaching techniques emphasize collaboration and peer support in an inclusive learning environment, while learning design includes effective program planning through curriculum modification, observation, and home visits.